Female chimpanzee associations with male kin: trade-offs between inbreeding avoidance and infanticide protection. (August 2022) - Wellens, Kaitlin R.; Lee, Sean M.; Winans, Jack C.; Pusey, Anne E.; Murray, Carson M.
Abstract : A large body of literature demonstrates the adaptive benefits of social relationships between kin, including fitness and survival. Given that most social mammals are characterized by male-biased dispersal, the majority of research on kin selection and associated advantages focuses on social relationships between female kin. Meanwhile, research on social relationships between adult male and female kin has primarily focused on inbreeding avoidance or the benefit to adult sons, with less attention on potential advantages these social relationships may provide females. The general pattern of male dominance over females in most mammal species suggests that females may benefit from protective associations with adult male kin. Using 43 years of behavioural data on the wild chimpanzees, Pan troglodytes schweinfurthii, of Gombe National Park, Tanzania, we examined association patterns between females and their adult maternal male kin. We specifically focused on how these associations may represent a trade-off between inbreeding avoidance and protection for females, particularly against infanticide. In accordance with inbreeding avoidance, we predicted that females' association with adult kin would decrease when they were maximally tumescent, signalling sexual receptivity. To determine whether female–male kin associations provide protection to females, we examined female associations with adult male kin during their first year postpartum when infants are most vulnerable to infanticide. We predicted that during this first year postpartum, females would have a higher association with male kin than with unrelated males. We found that females associated more with adult sons and brothers than with unrelated males when they did not have a sexual swelling. Female association increased with all males across tumescence but females associated less with their brothers than they did with their sons and unrelated males when they were maximally tumescent, providing equivocal support for the inbreeding avoidance hypothesis. Furthermore, females associated more with both sons and brothers than with unrelated males in the first 6 months of the postpartum period. Higher association with brothers, relative to unrelated males, persisted throughout the first year postpartum. Together, these results speak to the cost–benefit trade-off in female and adult male kin associations, highlighting the potential protective advantage for females, especially during the postpartum period. Highlights: We examined association patterns between females and their adult maternal male kin. Association with sons, brothers and unrelated males increased with swelling size. Association with sons was higher than with other males during early postpartum. Association with brothers was higher than with unrelated males 1 year postpartum. Our results suggest a potential male kin protective advantage postpartum.